Cold temperatures invert product ratios in Penning ionisation reactions with argon - Bibelnik, Natan; Gersten, Sasha; Henson, Alon B.; Lavert-Ofir, Etay; Shagam, Yuval; Skomorowski, Wojciech; Koch, Christiane P.; Narevicius, Edvardas (Molecular Physics, 2019)
In many chemical reactions with more than one possible outcome, the branching ratio, which is the ratio between the different reaction paths, is nearly constant over a wide range of collision energies. In barrierless systems governed by long-range interactions, however, the branching ratio is more sensitive to collision energy, and its dependence on it can be useful for better understanding the dynamics and reconstructing interaction potentials. Here we present the reaction rates of Penning and associative ionisation of metastable neon and helium with argon atoms. We obtain reaction rates in merge beam experiments, over a wide range of collision energies corresponding to that of room temperature, all the way down to a few millikelvins. We observe a change of two orders of magnitude in the branching ratio in the measured collision energy range and explain these changes using theoretical calculations.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Associative ionisation; Branching ratio; Cold collisions; Merged beam; Penning ionisation